Willingness to vaccinate against influenza A (H1N1)pdm09 among Brazilian civil servants: Pró-Saúde cohort study - Guilherme Loureiro Werneck; Eduardo Faerstein (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To investigate sociodemographic factors associated with the willingness to take the pandemic influenza vaccine. Methods: This is a cross-sectional study of Brazilian civil servants participating in the fourth wave (2012-2013) of the longitudinal Pró-Saúde Study. Associations were expressed as odds ratios (OR) and 95% confidence intervals (95%CI), estimated by multivariate logistic regression models. Results: Among 2,828 participants, 15.9% would not be willing to vaccinate in the future if the Brazilian Ministry of Health promoted a new vaccination campaign against pandemic influenza. Not willing to vaccinate in the future was strongly associated with not taking the pandemic influenza vaccine in 2010 (OR = 9.0, 95%CI 6.9 - 11.6). Among the unvaccinated, females, those aged > 60 years, and non-health care workers were less willing to vaccinate in the future. Again, in the vaccinated group, females were less willing to vaccinate. Conclusion: Multidisciplinary efforts should be encouraged in order to identify reasons for refusing vaccination, focusing on the individual and group perceptions of susceptibility, severity, benefits, and barriers to vaccination. Such information is needed to identify target groups for the delivery of customized interventions towards preventing emerging pandemics, such as avian influenza and COVID-19.